Identification of ignition system coil damage on MPV 1000 CC vehicle using fast fourier transform - Dayu Andryas Saputra; Subekti Subekti; Erlangga Yorda Agustin (JTTM : Jurnal Terapan Teknik Mesin, 2023)
The coil is the main component of the vehicle in the ignition system. Therefore it is necessary to anticipate to maintain the performance of the coil so that it continues to function properly. One method that can be done is the vibration method. Vibration testing was carried out on a 1000 cc MPV vehicle with rotational variations of 800 rpm, 1500 rpm, 2500 rpm and 3500 rpm. Vibration testing is carried out using an accelerometer sensor connected to the FFT Analyzer to measure the vibration response, then an analysis is carried out using Matlab. From the research results obtained at the Y-axis point with a rotating speed of 1500 rpm the first shape mode appears at a frequency of 45 Hz with an amplitude of 1.357 mm/s2 under normal conditions. Whereas in abnormal conditions the first shape mode appears at a frequency of 41 Hz with an amplitude of 1,944 mm/s2. In abnormal conditions, damage due to bearing defects is obtained, this is due to the discovery of a frequency of 4x rpm at 1500 rpm rotation. Furthermore, at a rotational speed of 2500 rpm the measurement results on the engine show that the first shape mode appears at a frequency of 48 Hz with an amplitude of 2256 mm/s2 in normal coil conditions. Whereas in abnormal conditions the first shape mode appears with a frequency of 41 Hz with an amplitude of 4.176 mm/s2. The frequency at 82 Hz under abnormal conditions shown under normal conditions does not appear. This shows the occurrence of losses, because it occurs at 2x rpm at 2500 rpm rotation